(untitled) (Revista Cientifica Ingenio Magno, 2022)
Abstract— Construction has evolved in the search for new techniques that allow the development of: greater resistance, lower costs, greater durability, ease of installation and finally the need for sustainable construction; In order to demonstrate these points, the evaluation of an existing design of a house of 45.6 m2 in the area of social interest was continued. As a result of this, prices were sought for the construction of APUS that implemented the budget that was divided into two parts, structure and masonry, since the comparison to be studied was based on these two chapters. From the previous point onwards, we proceeded with a statistical study that consisted of the revision of trends according to the behavior of the cost in the delay time in each of the projects worked, also from here the percentages of variation between both projects were extracted (block fast - w panel and traditional masonry), thus demonstrating in a quantitative way which was more feasible for this type of construction. Finally, the results were presented to detail the advantages and disadvantages of each of the systems.